Anticoagulant use to treat VTE (venous thromboembolism) in pregnancy: a review - Purwandityo, Ayuningtyas Galuh; Muhammad S. Finnegan; Mukarromah D. Putri; Muya Saroh; Nindita Rachmania; Riandita G. Putri (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is a medical condition that occurs when a blood clot forms in a deep vein that major cause of pregnancy-related maternal death. As pregnancy progresses, the risk of hypercoagulability increases, fibrinogen, factors VII, VIII, X and VWF (Von Willebrand Factor), plasminogen activator inhibitor-1, plasminogen activator inhibitor-2 are increases and 40-60% protein S decreases. Therefore, anticoagulant drugs are the mainstay of therapy for patients with VTE. The review aimed to select the best anticoagulant for pregnancy women with VTE. A scoping review was used. The type of articles reviewed were original articles obtained from four electronic journal databases published within 2012-2021. The main therapeutic agent recommended for use in the prevention and treatment of VTE in pregnancy is low molecular weight heparin (LMWH). LMWH has better bioavailability than other anticoagulants, has a lower risk of maternal bleeding, thromboembolic, thrombocytopenia and osteoporosis. The use of LMWH is actually better, more comfortable and safety for patients.